The prognostic impact of the detection of metastatic inferior mediastinal lymph node in nonsmall cell lung cancer at preoperative term. Issue 4 (2013) - Keskin, Hakan; Erdoğan, Abdullah; Zeybek, Arife; Dertsiz, Levent; Sarper, Alpay; Demircan, Abid
No abstract available